Influence of polychemotherapy on the morphology of metastases and kidney of resistant RLS-bearing mice - Zonov, E.V.; Voronina, E.I.; Zenkova, M.A.; Ageeva, T.A.; Ryabchikova, E.I. (Experimental Oncology, 2013)
Aim: Polychemotherapy (PCT), widely used for the antitumor treatment has a pronounced toxic effect on the organism, and its cytostatic effect sometimes is canceled by multidrug resistance of a neoplasia. Comprehension of the nature and development of pathological changes caused by the PCT during the treatment of cancer is very important to improve the efficiency of the therapy and to clarify the mechanisms of tumor-host interactions. This study was aimed to examine PCT impact on kidney cells and tissues in mice with transplanted resistant lymphosacroma (RLS) and to analyze morphology of metastases of the tumor in kidney during PCT. Materials and Methods: Male mice CBA/LacSto (55 animals) were intramuscularly implanted in the right hind paw by 105 cells/ml of tumor RLS (a diffuse large B-cell lymphosarcoma) with multi-drug resistance (MDR) phenotype. Mice received combination of cyclophosphamide (50 mg/kg), oncovin (0.1 mg/kg), hydroxydaunorubicin (4 mg/kg), and prednisone (5 mg/kg) accordingly to CHOP scheme each 7 days after inoculation of the tumor. The kidneys were sampled on days 1, 3 and 7 after each series of injection of PCT preparations and processed for light and electron microscopy, immunohistochemical analysis of Ki-67 and Apaf-1 proteins also was performed. Results: Tumor RLS produced metastases comprised of small cells in the kidneys of mice after 8 days post inoculation. Application of PCT resulted in destruction of small-cell metastases and development of many large-cell metastases in kidney. Application of PCT induced the development of prominent damage of nephron cells, primarily in S3 segments of proximal tubules. Even one series of PCT caused reduction of basal plasma folds in these cells and alteration of mitochondria. Damage of proximal tubules and involvement of distal tubules, renal bodies and interstitial tissue in the pathologic process, increased during the experiment. This work presents the description of morphological changes in kidney as well as of the tumor metastases under PCT influence. Conclusion: The obtained data should be considered while designing of remedies for recovery of internal organs functions after antitumor PCT.